2021
DOI: 10.3390/antiox10060902
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Oroxylin A on Retinal Ganglion Cells in Experimental Model of Anterior Ischemic Optic Neuropathy

Abstract: Nonarteritic anterior ischemic optic neuropathy (NAION) is the most common cause of acute vision loss in older people, and there is no effective therapy. The effect of the systemic or local application of steroids for NAION patients remains controversial. Oroxylin A (OA) (5,7-dihydroxy-6-methoxyflavone) is a bioactive flavonoid extracted from Scutellariae baicalensis Georgi. with various beneficial effects, including anti-inflammatory and neuroprotective effects. A previous study showed that OA promotes retina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…ROS expression has been reported in retinal ischemia or hypoxia, causing the loss of visual function and irreversible neuronal and axonal damage [46]. A previous study confirmed that increasing Nrf2 protein expression maintained the viability of RGCs in an rAION model [19,34]. In addition, Nrf2 activators have been approved by the FDA as drugs to treat kidney disease and relapsing-remitting multiple sclerosis [47][48][49].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…ROS expression has been reported in retinal ischemia or hypoxia, causing the loss of visual function and irreversible neuronal and axonal damage [46]. A previous study confirmed that increasing Nrf2 protein expression maintained the viability of RGCs in an rAION model [19,34]. In addition, Nrf2 activators have been approved by the FDA as drugs to treat kidney disease and relapsing-remitting multiple sclerosis [47][48][49].…”
Section: Discussionmentioning
confidence: 92%
“…Previous research has documented that ED-1-positive cells are found during ischemic injury to the optic nerve [ 19 , 34 ], enhancing microglia/macrophage transfer to their activated forms in order to secrete inflammatory cytokines and activate inflammation [ 50 ]. However, overactivated microglia provide excessive amounts of the inflammatory ligands IL-6, IL-1β, and TNF-α, causing ROS, iNOS, NFκB, and NLRP3 inflammatory complex activation; additionally, disruption of neuronal homeostasis was observed in ischemic optic neuropathy [ 11 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OA markedly decreased the apoptosis of RGCs and optic disc edema and upregulated the Nrf2 signaling pathway and its downstream antioxidant enzymes NAD(P)H: quinone oxidoreductase (NQO-1) and HO-1 in the retina. Hence, OA can be efficiently used as a therapeutic drug candidate in the NAION [ 179 ].…”
Section: Oa For Eye Diseasesmentioning
confidence: 99%